ANALISIS PENGGUNAAN APLIKASI WHATSAPP DALAM PEMBELAJARAN ONLINE KELAS V MADRASAH IBTIDAIYAH PERSATUAN UMAT ISLAM (PUI) HAURKOLOT INDRAMAYU - Kasiun Kasiun; Abdur Rahim; Anjar Sulistyani (Bajang Institute, 2023)
In the midst of the current pandemic situation, the process of learning activities must still be carried out even though not directly face to face. Of course, this phenomenon requires the right media in online learning, namely WhatsApp. WhatsApp as a medium to support the implementation of online learning at the PUI Haurkolot Madrasah Ibtidaiyah is from this phenomenon the author raised this title. This study aims to find out 1) To find out the analysis of the use of the WhatsApp application in online learning for class V Madrasah Ibtidaiyah Islamic Community Association Haurkolot Indramayu 2) To find out the obstacles to using the WhatsApp application in online learning for class V Madrasah Ibtidaiyah Islamic Community Association Haurkolot Indramayu. This research method uses a qualitative descriptive approach using a qualitative naturalistic approach. the object of this study was Class Teachers and Class V Students of the Haurkolot Islamic Association (PUI) Madrasah Ibtidaiyah. The data source for this research uses primary data and secondary data. Data collection procedures use observation, interviews and documentation. The results of the study show that the use of the WhatsApp application in online learning is very helpful in the process of conveying information about the material to be studied. In addition, the WhatsApp application is a means of learning activities, so that the learning process becomes more effective and provides convenience to teachers and students in the communication process during online learning. Obstacles in using the WhatsApp application in online learning are signal interference which makes it difficult to access WhatsApp, another obstacle is the lack of effectiveness of the learning process the teacher cannot directly see the seriousness of students, cellphone memory which quickly fills up with documents that are difficult to enter will be hampered.